A cross‐sectional study of community‐level physician retention and hospitalization in rural Ontario, Canada. Issue 1 (15th March 2022) - Mathews, Maria; Ouédraogo, Alexandra M.; Lam, Melody; Gozdyra, Peter; Green, Michael
Abstract: Purpose: Many rural communities experience poor family physician retention. We examined the association between community‐level physician retention and hospitalization for all causes and ambulatory care‐sensitive conditions (ACSCs) in 2017 among residents of rural communities in Ontario, Canada. Methods: We conducted a population‐based cross‐sectional study by linking administrative data from the public health insurance program in Ontario. To create the physician retention measure for each rural community, we divided the number of family physicians who worked in the community in both 2016 and 2017 by the total number of unique family physicians in the community in either year. We grouped retention level by tertile and added a fourth category, "no physician" to include communities that did not have any residing physicians in either 2016 or 2017. Outcomes were all‐cause hospitalization and ACSC hospitalization between April 1, 2017 and March 31, 2018. Findings: Among 1, 436, 794 rural residents, there were 93, 752 all‐cause hospitalizations and 8, 691 ACSC hospitalizations in 2017. After controlling for other predictors, compared to residents in low‐retention communities, residents of medium‐ and high‐retention communities were 0.888 (95% CI: 0.868‐0.909) and 0.937 (95% CI: 0.915‐0.960) times as likely to have all‐cause hospitalization, and residents of high‐retention communities were 0.918 (95% CI: 0.858‐0.981) times as likely to have ACSC hospitalization in 2017. Conclusions: Community‐level physician retention is significantly associated with all cause and ACSC hospitalization in rural communities in Ontario, and may serve as an alternate measure to assess the impact of disrupted continuity of care.